Effect of rGO synthesized from different precursors on the enhancement in mechanical properties of GFRPs - Anushka Garg; Soumen Basu; Roop L. Mahajan; Rajeev Mehta (Scientific Reports)
Abstract This study investigates and compares the impact of various precursor-based reduced graphene oxide (rGO) nanofillers, prepared through chemical and thermal reduction methods on the mechanical properties of E-glass fiber-reinforced epoxy resin composites (GFRPs). Varying amounts of rGO derived from semi-anthracite coal-based graphene oxide (AC-rGO) and graphite-based graphene oxide (Gr-rGO), synthesized via thermal reduction and chemical reduction (AC-GT, Gr-GT, AC-GC, and Gr-GC) into an epoxy resin matrix were dispersed into an epoxy resin matrix. The resulting mixture was infused into E-glass fiber mats to fabricate multiscale composites using vacuum-assisted resin infusion molding technique. The most notable improvements were observed in the thermally reduced graphene synthesized from anthracite coal (AC-rGO)-reinforced GFRPs at a loading of 0.25 phr (parts per hundred resin), with enhancements of 13.4% in flexural strength, 25% in tensile strength, and 21.5% in impact strength. The corresponding improvements for the chemically reduced graphene synthesized from AC-GO, AC-GC-reinforced GFRPs were 9.4%, 23.4%, and 14.1%, respectively. In contrast, for chemically and thermally reduced Gr-rGO-reinforced GFRPs the flexural strength increased by 15.7% and 14.4%, tensile strength by 20% and 22.2%, and impact strength by 16.4% and 7.5%, respectively. A similar trend was observed for interlaminar shear strength (ILSS) testing. To understand the observed differences with various GO precursors, XRD, SEM, and FTIR analyses were conducted. The increment in mechanical properties for AC-rGO-reinforced GFRP is almost equivalent to or greater than Gr-rGO-reinforced GFRP, regardless of the synthesis method used. The enhanced mechanical properties, including high strength, lightweight characteristics, and cost-effectiveness, are essential for a range of applications.